(untitled) (Research, Society and Development, 2021)
Introduction: Vulnerability, loss of women’s autonomy in a delivery room and obstetric violence, such as mistreatment, disrespect, abuse and neglect by the health professionals’ team. The same brings as a general objective: To identify how obstetric violence against women is reproduced, the context and implications of their condition of vulnerability, having as specific objective: To describe the importance of listing strategies (health education) and empowerment the autonomy of women, from prenatal to delivery room, analyzing comprehensive care during prenatal care, respecting the desires of the parturient, which would mitigate in situations of obstetric violence. Methodology: This is a study with a qualitative approach, descriptive, integrative review type. Data collection was performed at the Virtual Health Library (VHL), where four databases were identified: BDENF; LILACS; MEDLINE; Colecionasus; the descriptors (Decs) used were: obstetric violence; health education; health professionals. The final sample was composed of 9 articles published from 2015 to 2019, written in Portuguese and after filtering the inclusion and exclusion criteria, 05 articles were used. In the data analysis, three categories were established: 1: Comprehensive concept of violence; 2: Violence against women in Brazil and 3: Obstetric violence. We conclude that obstetric violence against women can occur from prenatal to childbirth and that vulnerability makes them susceptible to abusive practices. However, the knowledge acquired innatal, the bond, trust and safety created between health professional and patient transform them into women able to identify when they are not being treated properly which decreases the rate of violence in childbirth and improve pregnancy.